S-04-4: INCONSISTENT GUIDELINES-BASED CONTROL STATUS OF OFFICE, HOME, AND AMBULATORY BLOOD PRESSURE MEASURED BY AN ALL-IN-ONE BP MONITORING DEVICE. (January 2023) - Kario, Kazuomi; Hoshide, Satoshi; Tomitani, Naoko; Nishizawa, Masafumi; Yoshida, Tetsuro; Kabutoya, Tomoyuki; Fujiwara, Takeshi; Mizuno, Hiroyuki; Narita, Keisuke; Komori, Takahiro; Suzuki, Daisuke; Nakazato, Jun; et al.
Abstract : Objective: Inconsistencies between office and out-of-office blood pressure (BP) values (described as white-coat hypertension or masked hypertension) may be attributable in part to differences in the BP monitoring devices used. We studied the inconsistency of the classification of BP control (well-controlled BP vs. uncontrolled BP) among office, home, and ambulatory BPs by using a validated all-in-one BP monitoring device. Design and method: In the nationwide, general practitioner-based multicenter HI-JAMP study, 2, 322 hypertensive patients treated with antihypertensive drugs underwent office BP measurements and 24-h ambulatory BP monitoring (ABPM), consecutively followed by 5-day home BP monitoring (HBPM), using the same all-in-one device over a total of seven BP measurement days. Results: Using the thresholds of the JSH2019 and ESC2018 guidelines, the subjects with consistently well-controlled office (<140mmHg) and home systolic BP (SBP) (<135mmHg) (n = 970) also tended to have well-controlled 24-h SBP (<130mmHg) (n = 808, 83.3%). The subjects with consistently uncontrolled office and home SBP (n = 579) also tended to have uncontrolled 24-h SBP (n = 444, 80.9%). Among the subjects with inconsistent classifications of office and home BP control (n = 803), 46.1% had inconsistent ABPM-vs.-HBPM out-of-office BP control status. When the 2017 ACC/AHA thresholds or JSH2019 target BP thresholds were applied as an alternative, the results were essentially the same. Conclusions: The combined assessment of office and home BP is useful in clinical practice. Especially for patients whose office BP classification and home BP classification conflict, the complementary clinical use of both HBPM and ABPM might be recommended.